2021
DOI: 10.7554/elife.62645
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid fuels pancreatic cancer cell growth

Abstract: Rewired metabolism is a hallmark of pancreatic ductal adenocarcinomas (PDA). Previously, we demonstrated that PDA cells enhance glycosylation precursor biogenesis through the hexosamine biosynthetic pathway (HBP) via activation of the rate limiting enzyme, glutamine-fructose 6-phosphate amidotransferase 1 (GFAT1). Here, we genetically ablated GFAT1 in human PDA cell lines, which completely blocked proliferation in vitro and led to cell death. In contrast, GFAT1 knockout did not preclude the growth of human tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 62 publications
0
43
0
Order By: Relevance
“…This phenomenon was also observed in endocardial endothelial cells, wherein HA endocytosis works as high-energy metabolites to fuel cells [ 142 ]. Recently, a researcher reported that an increase of GlcNAc from HA cleavage remarkably ensures the energy supply in growth of pancreatic cancer cells [ 143 ].…”
Section: Pre-metastatic Barometer In the Tumor Microenvironmentmentioning
confidence: 99%
“…This phenomenon was also observed in endocardial endothelial cells, wherein HA endocytosis works as high-energy metabolites to fuel cells [ 142 ]. Recently, a researcher reported that an increase of GlcNAc from HA cleavage remarkably ensures the energy supply in growth of pancreatic cancer cells [ 143 ].…”
Section: Pre-metastatic Barometer In the Tumor Microenvironmentmentioning
confidence: 99%
“…In breast cancer, HA production shifts metabolic programs toward acceleration of glycolysis, [50] which is regulated by HIF-1 under the control of the hexosamine biosynthetic pathway flux. [51] Consistently, it has been reported that antagonizing hyaluronan-CD44 interactions with HA oligomers inhibits the assembly of MCT1 and MCT4 complexes in the plasma membrane, and consequently suppresses lactate efflux from breast carcinoma cells [52] . In addition, one Phase 1 trial of PEGPH20 evaluating 18 F-FDG-PET/CT showed that 6 out of 9 evaluable patients exhibited decrease in standardized uptake value (SUV), suggesting an upregulation of glycolysis [41] .…”
Section: Discussionmentioning
confidence: 68%
“…The combination of PGM3 inhibitor FR054 and GEM increases chemosensitivity and effectively inhibits xenograft tumor growth ( Ricciardiello et al, 2020 ). A recent study showed that hyaluronic acid in PC bypass GFAT1 and promote PC cell growth by replenishing energy for HBP through the GlcNAc salvage pathway ( Kim et al, 2021 ).…”
Section: Alterations In Glucose Metabolismmentioning
confidence: 99%